Self-Harm Thoughts Postpartum as a Marker for Long-Term Morbidity - Iliadis, Stavros I.; Skalkidou, Alkistis; Ranstrand, Hanna; Georgakis, Marios K.; Axfors, Cathrine; Papadopoulos, Fotios C. (Frontiers in Public Health, 2018)
Introduction: Postpartum depression predisposes to maternal affective and somatic disorders. It is important to identify which women are at increased risk of subsequent morbidity and would benefit from an intensified follow-up. Self-harm thoughts, with or without other depressive symptomatology, might have prognostic value for maternal health beyond the postpartum period. Aim: To investigate the somatic and psychiatric morbidity of postpartum women with self-harm thoughts, with or without other depressive symptoms, over a 7-year follow-up period. Materials and methods: The subjects for this study are derived from a population-based Swedish cohort of women who gave birth at Uppsala University Hospital (May 2006-June 2007) and who answered the Edinburgh Postnatal Depression Scale (EPDS) at five days, six weeks and six months postpartum. Three groups were included: women reporting self-harm thoughts (SHT group, n=107) on item 10 of the EPDS; women reporting depressive symptoms, i.e. EPDS≥12 at six weeks and/or six months postpartum, without self-harm thoughts (DEP group, n=94); and randomly selected controls screening negatively for postpartum depression (CTL group, n=104).The number of diagnostic codes for somatic and psychiatric morbidity, according to the International Statistical Classification of Diseases and Related Health Problems (ICD) system, and the number of medical interventions, were retrieved from medical records over seven years following childbirth and were used as the outcome measures, together with any prescription of antidepressants and sick-leave during the follow-up. Results: The SHT group had the highest psychiatric morbidity of all groups and more somatic morbidity than controls. Affective disorders were more common in the SHT and the DEP group compared with controls, as well as antidepressant prescriptions and sick-leave. One fifth of women with self-harm thoughts did not screen positive for depressive symptoms; nevertheless, they had more somatic and psychiatric morbidity than the control group. Conclusion: Women reporting thoughts of self-harm in the postpartum period are at increased risk of somatic and psychiatric morbidity during a follow-up of seven years after delivery and this increased risk may not be fully attributed to depressive symptoms. Results underline the importance of screening for self-harm symptoms postpartum and point to a need for individualized follow-up.